Experimental study on preparation the player specialized as a goalkeeper in the under 16 football game - Grosu Bogdan-Marius (Editura Univeristatii "Stefan cel Mare" din Suceava, 2022)
The optimization of means of action in the specific training of the football goalkeeper at the age of under 16 must be based on a content of means in training of more than 60% context of adversity.